An Analysis of Corruption and Inefficiency in Nigerian Public Service: Islamic Point of View - Sidi Attahiru, Mustapha (International Journal of Scientific Research and Management (IJSRM), 2022)
This research aims to determine the effect of corruption on Inefficiency in the Nigerian public sector from Islamic point of view. This is because corruption has adversely affected the socio-cultural, political and economic development of Nigeria.The survey was conducted at Sokoto State Nigeria. Primary data was collected and SmartPLS 3 version was used for the analysis. 150 questionnaires were distributed to the senior staff of Local Government Service Commission, Sokoto, but only 96 were used for the analysis. The study found that there is significant relationship between corruption and inefficiency in Nigeria’s public service. The study also established that inefficiency that bedevilled the public service is as a result of corruption. This research is significant as there is dearth of literature on Islamic approach linking inefficiency to corruption in Nigeria. While this paper sets the stage, there is however, the need for future research.